A meta-analysis of the effects of cognitive behavioral therapy on quality of life and negative emotions of informal cancer caregivers - Zhou, Shuang; Wang, Yumei; Wang, Qiang; Yang, Guodong; Ren, Huipeng; Bao, Yanping (Frontiers in Psychiatry, 2022)
Objective: This study aimed to systematically review the effect of cognitive behavioral therapy (CBT) in terms of improving the quality of life (QOL) and negative emotion of informal cancer caregivers. Methods: PubMed, Cochrane Library, EMBASE, Web of Science, MEDLINE, China National Knowledge Infrastructure (CNKI) and China Biology Medicine disc (CBMdisc) were searched from the database establishment to October 2021. Literature screening, data extraction, and quality evaluation were conducted based on inclusion and exclusion criteria. Stata 14.0 software was used for data analysis. Results: A total of 17 randomized controlled trials (RCTs) involving 2348 cancer informal caregivers (CGs) were included in this study, with an overall loss rate of 13.3%. Meta-analysis showed no statistically significant difference in the impact of CBT on QOL (SMD= 0.28, 95%CI: -0.09~0.65, P<0.001). However, the improvement of depression in CBT intervention group was significantly better than that in control group (SMD= -0.32, 95%CI: -0.56~ -0.07, P=0.010). The HADS subgroup showed differences in depression scores (SMD= -0.80, 95%CI: -1.30~ -0.29, P=0.002). The overall effect of CBT on anxiety was statistically different, the improvement of anxiety in CBT intervention group was significantly better than that in control group (SMD= -0.36, 95%CI: -0.720~0.004, P=0.047). Conclusions: CBT had a positive effect on reducing depression and anxiety in informal cancer caregivers, and the effect on quality of life was not statistically significant, but showed a positive trend.